Hubungan Shift Kerja dengan Kelelahan Kerja pada Radiografer di Rumah Sakit Umum Daerah Teluk Kuantan - Purnamasari, Devi; Erindah, Putri; Annisa, Annisa; Tonis, Marian (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
A hospital is a health service institution that operates 24 hours a day. The service is divided into several sections, one of which is the medical support section, including radiology. Radiology workers are referred to as radiographers. In carrying out their duties, the radiographer cannot be separated from the work shift system, at the Teluk Kuantan Regional General Hospital applying morning shifts (07.00-14.00), afternoon (14.00-20.00) and night (20.00-08.00). Shift work time from morning, afternoon and evening can result in work fatigue. The purpose of this study was to see whether there is a relationship between work shifts and work fatigue on radiographers at the Teluk Kuantan Regional General Hospital. This research is a type of quantitative research that is analytic in nature with a cross sectional design through library research, field observations, questionnaires / questionnaires distributed to respondents. This research was carried out at the Radiology Institute of the Kuantan Bay Regional General Hospital from April to June 2022. The results of this study can be known by distributing questionnaires after which the data is processed using univariate and bivariate (Chi-Square) tests. Based on the bivariate test (Chi-Square) it is known that the value of p (value) = 0.003 where p (value) <0.05, meaning that there is a relationship between work shifts and the occurrence of fatigue in radiographers at the Teluk Kuantan General Hospital.